PENERAPAN METODE BERCERITA DENGAN MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN BAHASA JAWA ANAK KELOMPOK A DI BUSTANUL ATHFAL BAITUL MAKMUR KECAMATAN DAU KABUPATEN MALANG (Jurnal Dewantara, 2020)
The ability of children in language is one of the important things because with that language, children can communicate with parents, friends and people around them. Early childhood has a great curiosity and likes to tell new experiences they experienced. In the delivery of stories, children more fluent in Indonesian than in Jawkarenaa even though they come from Javanese descent. The introduction of Javanese language is very necessary in early childhood because Javanese has a level of use as a sense of respect or respect for older people in communication. Speaking Javanese in Bustanul Athfal Baitul Makmur, Dau sub-district, Malang regency is applied by the method of storytelling in learning so that children do not get bored and understand better with media images. Through a qualitative approach and type of classroom action research carried out with 4 stages, namely: 1. The planning stage, 2. The implementation phase, 3. The observation phase, 4. Reflection. With the subject of research group A children in Bustanul Athfal Baitul Makmur, Dau district, Malang regency has difficulty speaking Javanese. From 11 children in one class, only 2 children can speak Javanese. Data collection techniques using observation and documentation. Researchers as planners, implementing class actions directly involved in it, analyzing, reporting research results. Based on observations of cycle 1 and cycle 11, it was concluded that the application of the method of storytelling using picture media could improve the ability of group A children in Bustanul Athfal Baitul Makmur, Dau district, Malang district. This can be seen from cycle I by 27% increasing in cycle II to 64% or from 2 children to 8 children who can speak Javanese, with a minimum completeness criterion the value obtained by children> 2 is developing as expected (BSH).